PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE HIBRID TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIKA SISWA KELAS VIII SMP NEGERI 1 KOTANOPAN - Nurdalilah Nurdalilah (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2018)
This research aims to determine the influence of hybrid learning model to communication mathematics junior high school students. This research is a quantitative with experimental methods in the form of pure experiment types. The population were all eighth grade students at Public Junior High School 1 of Kotanopan, , Mandailing Natal Regency,North Sumatera Province in 2017/2018. The number of samples uses 37 persons as experimental class and 35 persons as control class. This research is a pure experiment using a pretest-posttest control group. In this study, the data collection method used is the testing techniques. Based on the analysis can be concluded that there is a significant effect on communications hybrid learning model mathematics junior high schoolstudent.Keywords: Hybrid Learning Model; Capability Concept Training Mathematics; Mathematical Communications Skills.